Modeling of SO2 emissions from Yatağan power plant - İm, Ulaş. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2003., 2003)
The meteorological model, CALMET, and its plume dispersion model, CALPUFF, were used in order to simulate the dispersion of SO2 emitted from Yatağan Power Plant and its effect on Yatağan district in the episodic event on December 2 and 3, 2000. CALMET was used to predict the hourly meteorological fields for 96 hours, starting from December 1, 2000, to December 4, 2000, while CALPUFF was used to predict the hourly ground level SO2 concentrations over a region of 15 km x 15 km grid with 1 km resolution. The meteorological data were obtained from two meteorological stations: surface data from Yatağan Meteorological Station, and upper air data from Isparta Meteorological Station. The emission data was taken from Yatağan Power Plant. It is found that south westerly and light winds and the nighttime surface inversion layers lead to accumulation of pollutants over Yatağan district. The results are compared with the measurements done by Local Environmental Authorities of Muğla. The simulation results indicate that the maximum ground level concentrations were found northeast from the source, which agrees with experimental measurement. On the other hand, the magnitude of results obtained with the model shows some differences compared with experimental measurements. The SO2 concentration levels are calculated to be very high in the morning hours of December 2 and 3, 2000. Overall, the results indicate that Yatağan district suffered seriously on these days. The sensitivity analysis showed that the concentrations are directly proportional to the emission rates, but wind speed is the most significant meteorological parameter on air pollution modeling compared to other meteorological parameters.
Keywords: Meteorology -- Observations.